Hepatitis A outbreak among men who have sex with men (MSM) in England, 2016–2018: The contribution of past and current vaccination policy and practice. (11th April 2019) - Plunkett, James; Mandal, Sema; Balogun, Koye; Beebeejaun, Kazim; Ngui, Siew Lin; Ramsay, Mary; Edelstein, Michael
Abstract: Background: We report on an outbreak of hepatitis A among men who have sex with men (MSM) in England and its associated healthcare resource burden, the strategies used to control the outbreak and the role of past and current hepatitis A vaccination policy and practice in England. Methods: National surveillance of hepatitis A, including reference laboratory confirmation and molecular sequencing, and a case questionnaire, was enhanced in 2017 to collect demographic and risk information, disease severity and healthcare utilisation. National Health Service (NHS) data was used to calculate associated healthcare costs. Results: During the outbreak period (July 2016 to January 2018), 670 confirmed cases were identified in England, caused by three distinct viral strains. The public health response included raising public and professional awareness, reinforcing vaccine recommendations for MSM, contact tracing for post-exposure vaccination, and mass community vaccination where spill-over of infection into the general population occurred. Hepatitis A vaccine was centrally procured to ensure sexual health clinics in England could offer vaccination to MSM. Outbreak associated healthcare costs were estimated to be approximately £1, 500, 000. Conclusions: While MSM are at increased risk of hepatitis A infection, inconsistent implementation of MSM vaccination policy in previous years led to an increasingly susceptible MSM population. The large number of cases, hospital admission rate and public health actions contributed to a significant healthcare burden. Recommending hepatitis A vaccination for MSM and clarifying commissioning responsibilities is essential to prevent future outbreaks.